ANALISYS OF DREDGING PROJECT CONTRACT TO AVOIDING THE DISPUTES - Japril Japril (Lambung Mangkurat University Press, 2015)
Dredging is one of the construction works with high level of uncertainty, which is potential to cause disputes between the service user (owner) and the service provider (contractor). Dredging in the private ports owned by PT. Indocement Tunggal Prakarsa Tbk. has been carried out four times since 1996 to 2013. Two of the projects ended with a dispute. Therefore, it is necessary to study the factors that led to disputes and to choose the most suitable model of contract for dredging work.The method applied is the Analytic Hierarchy Process (AHP). The analysis process begins with a literature study to determine criteria and sub-criteria for avoiding disputes, to determine an alternative of the most suitable model of contract for dredging projects, and to create a hierarchical structure. A questionnaire was later compiled based on the hierarchy. Questionnaires were conducted involving 20 respondents consisting of individuals who have had experiences as executors on dredging projects at PT. Indocement Tunggal Prakarsa Tbk, and had positions as project managers, field managers and executing supervisors.The result shows that the most important criterion to avoid disputes on the dredging project is Technical and Quality Aspects, weighing 43% of interest. The most important sub-criterion is Fixed Design Factor, Complete and Accurate Picture, weighing 75% of interest. The alternative contract model to select with the highest importance weight is Lump Sum Fixed Price contract, the importance weight from the respondents is 53% and the weight of the interests by experts was 49%. Therefore, to avoid disputes on the dredging project, the most suitable contract model is the Lump Sum Fixed Price.